2005
DOI: 10.1097/01.sla.0000167759.15670.14
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Axillary Dissection to No Axillary Dissection in Older Patients With T1N0 Breast Cancer

Abstract: Older patients with T1N0 breast cancer can be treated by conservative breast surgery and no axillary dissection without adversely affecting breast cancer mortality or overall survival. The very low cumulative incidence of axillary events suggests that even sentinel node biopsy is unnecessary in these patients. Axillary dissection should be reserved for the small proportion of patients who later develop overt axillary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(86 citation statements)
references
References 25 publications
2
79
0
5
Order By: Relevance
“…We identified 2133 potentially relevant articles in the primary literature search (Figure 1), three RCTs (Martelli et al, 2005;IBCSG et al, 2006;Krag et al, 2010) that met the inclusion criteria and included a total of 5,337 old woman with breast cancer and were published in English. The basic characteristic of the studies included cases, tumor size, ER status, follow-up period, interventions and outcomes (Table 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…We identified 2133 potentially relevant articles in the primary literature search (Figure 1), three RCTs (Martelli et al, 2005;IBCSG et al, 2006;Krag et al, 2010) that met the inclusion criteria and included a total of 5,337 old woman with breast cancer and were published in English. The basic characteristic of the studies included cases, tumor size, ER status, follow-up period, interventions and outcomes (Table 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…Whether sentinel node-positive disease is then treated with full surgical dissection or primary radiotherapy appears to be center specific, and no clear guidelines exist for this in the elderly population [4]. Finally, one study illustrated that older women aged 65-80 with clinically small, lymph node negative (T1N0) tumors may not require even sentinel lymph node biopsy; patients in that trial were randomized to breast surgery with or without axillary dissection and there was no difference in survival between the two groups at 60 months, and Ͻ2% of patients in the no axillary dissection arm developed axillary disease [15]. It is important to note, however, that most patients in that study had other favorable tumor characteristics (low grade, strongly hormone sensitive).…”
Section: Elderly Women and Breast Cancer Surgerymentioning
confidence: 99%
“…These patients are spared the adverse effects of ALND without adverse oncologic outcome in the short term. Nevertheless even these studies suggest that axillary recurrences are much more frequent (up to three times) if no axillary intervention is undertaken, although low in absolute numbers [15,16] . In addition another study with the same design that included younger patients (mean age 62 years old) showed a statistically significant worse overall and disease-free survival in patients with no axillary intervention as compared with the group that underwent ALND [17] .…”
Section: Introductionmentioning
confidence: 99%
“…For example in a small study of 47 patients with positive SLN (33 with micrometastases only) and a low risk of 11.5% of additional LN positivity by the MSKCC model two patients (4.2%) had an axillary recurrence [14] . On the other hand, as studies performed before the routine introduction of SLN biopsy that compare ALND with no dissection in older patients (mean age over 70 years old) with small primaries (mostly T1a and T1b), ER positive and clinically negative axilla have shown, most patients with a predicted low burden axillary disease will not have a clinically apparent axillary recurrence even if left untreated [15,16] . These patients are spared the adverse effects of ALND without adverse oncologic outcome in the short term.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation